1965
DOI: 10.1152/ajplegacy.1965.209.3.593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hemoglobin type on the cardiorespiratory system of sheep

Abstract: In domestic sheep there exist two genetically determined types of hemoglobin which have considerably different oxygen affinities. Under most conditions sheep with either of these hemoglobins exist together, apparently sheep with one type being at no gross disadvantage compared to those with the other. Theoretical considerations suggested that the tissues of sheep with the higher oxygen affinity hemoglobin (Hb-A) should be hypoxic relative to those of sheep with the lower oxygen affinity hemoglobin (Hb-B). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
1

Year Published

1966
1966
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 0 publications
2
14
1
1
Order By: Relevance
“…are similar to those reported for anaesthetized sheep by Dawson and Evans (1967), while those obtained during disturbance (9-6 g/100 ml ± 0-6 S.D.) approximate values published for conscious sheep (Holman, 1944;Tod, Wyant, Stone and Elam, 1952;Dawson and Evans, 1965). In our study the increase in jngular haemoglobin eoneentration during disturbance varied from test to test, ranging between 12^ and 30%.…”
Section: Discussionsupporting
confidence: 92%
“…are similar to those reported for anaesthetized sheep by Dawson and Evans (1967), while those obtained during disturbance (9-6 g/100 ml ± 0-6 S.D.) approximate values published for conscious sheep (Holman, 1944;Tod, Wyant, Stone and Elam, 1952;Dawson and Evans, 1965). In our study the increase in jngular haemoglobin eoneentration during disturbance varied from test to test, ranging between 12^ and 30%.…”
Section: Discussionsupporting
confidence: 92%
“…Other physiological parameters relative to oxygen affinity have been examined. Dawson & Evans (1965) found that both the arterial and venous bloods of sheep with HbA were significantly more saturated with oxygen than those of sheep with HbB. Also the former sheep had a larger blood volume, and higher values for haemoglobin and packed cell volume than the latter.…”
Section: ( 5 ) Possible Signijicance Of Haemoglobin Polymorphismmentioning
confidence: 86%
“…This interesting and concentrated distribution of the HBA allele in the Tibetan sheep surveyed may not be related directly with such a phylogenetic study. Rather, it has long been considered that the hemoglobin A component, which is controlled by the HBA allele, has a high affinity for oxygen (Dawson and Evans, 1965) and is important for survival in mountain areas at altitudes over 3000 m. This physiological adaptability will likely be associated with the specific distribution of the HBA allele in the Tibetan sheep group. According to Zhang et al (1988), it has been demonstrated that the frequency of the HBA allele clearly increases with the rise in the altitude of the grazing areas of the Menyuan Tibetan sheep of Qinghai Province.…”
Section: Discussionmentioning
confidence: 99%